Beyond audit : auditing remotely and delivering value - Mainardi, Robert L., 1964- (Wiley corporate F&A, 2021)
"Change has been thrust upon the audit industry and every company must adapt. With the business interruption and remote work environments, this is the perfect time for audit departments to step back and turn the critical eye on their own operations. As businesses come back to "normal" (probably in the new year), audit department should identify how to increase their product offerings and build the most effective and efficient operations to partner with their clients in the revised work environments. This book is designed to take an auditor from a foundational understanding of not only the current status of the business environment, but also a reflective review of their own operational effectiveness and efficiency. It will include a detailed methodology -- from planning to action item development -- to be followed to ensure clear identification and agreement (with the business partner) of the business objectives and corresponding "true process risks" so testing remains focused and value added. Furthermore, critical skills will be discussed as well as team development and learning at every position level. While benefits are detailed in every chapter, the most valuable enhancement to audit departments around the world will be in the introduction of the Audit Risk Barometer (ARB). The ARB is an innovative self-assessment tool which scores and scales individual audit department strengths and opportunities for improvement. This book will incorporate links to online video summaries where the reader can watch supporting stories specifically about examples referenced in the book as well as get introduced to the risk barometer and the templates mentioned throughout the book. These summaries will include interviews with experienced professionals, template explanations, technique comparisons and recommendations, success and failure examples, and a software tool to assist audit teams in not only documenting their work but also, capturing and tracking key department metrics for early identification of deviations from the standard"- Resumé vydavatele